Entendiendo al consumidor japonés y coreano. Tendencias de exigentes mercados en Asia (2014)
With economies that grow and develop rapidly, East Asia attracts the eyes of industrialized and developing countries, as well as large business conglomerates and ambitious entrepreneurs willing to venture into their markets with the desire to find opportunities and profits to Your corporations There are many attractions that the region offers, including economies with high purchasing power - especially South Korea and Japan -, the concentration of a large percentage of the world's population, stable growth rates and an increasingly specialized and westernized consumer . Regardless of the degree of development they have achieved, the innumerable mistakes that companies make when they arrive in the region cannot be set aside, so they understand very well the performance of economies, policies, dynamics and the way in which Behave your consumers is vital if you want to succeed in these demanding, changing and globalized markets. This document presents a recent economic analysis of South Korea and Japan, then some elements of the trends and behaviors of its inhabitants are contextualized.